2019
DOI: 10.1016/j.abd.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Causative drugs for drug-induced cutaneous reactions in central China: a 608-case analysis

Abstract: BackgroundReports regarding the causative drugs of drug-induced cutaneous adverse reactions in China are indistinct, such that different regions have reported the spectrum of drugs differs substantially in different clinical conditions.ObjectiveTo explore the causative drugs that led to cutaneous reactions.MethodsAdverse drug reaction reports from central China were collected and divided into cutaneous adverse reactions and severe cutaneous adverse reactions groups. Cases were reviewed retrospectively for caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
(19 reference statements)
0
12
4
1
Order By: Relevance
“…For example, using a highly sensitive method first may capture the most true positive cases (eg, algorithmic approach), followed by a highly specific method to rule out the greatest number of true negatives (eg., probabilistic method). 3,30,31 Investigations: Lab-Based, Pharmacogenomic and Confirmatory Testing…”
Section: Causality Assessment Methodsmentioning
confidence: 99%
“…For example, using a highly sensitive method first may capture the most true positive cases (eg, algorithmic approach), followed by a highly specific method to rule out the greatest number of true negatives (eg., probabilistic method). 3,30,31 Investigations: Lab-Based, Pharmacogenomic and Confirmatory Testing…”
Section: Causality Assessment Methodsmentioning
confidence: 99%
“…3 Obat penyebab tersering adalah obat antiinflamasi nonsteroid (OAINS), 4,5 golongan sulfa, 6,7 antibiotik laktam, antikonvulsan (misalnya karbamazepin, fenobarbital, dan fenitoin), antiretrovirus, agen kontras, alopurinol, dan lainlain. 8,9 Kerusakan jaringan pada NE terjadi akibat apoptosis sel keratinosit yang diinduksi oleh stimulus stres, kerusakan DNA, dan sitokin intraselular. 2,3 Insidens terjadinya SSJ diperkirakan 1-6,5 kasus per juta orang per tahun.…”
Section: Pendahuluanunclassified
“…A study by Yampayon et al reported that omeprazole comedication was strongly associated with phenytoininduced DRESS in Thai patients [59]. A study by Zhao et al showed that patients taking multiple-drug combinations and with a complex medication history, which greatly contributed to the development of SCARs [64]. The use of multiple drugs results in the accumulation of drugs, reactive metabolites, and drug interaction because of excessive demands on enzyme systems for oxidation or acetylation of multiple drugs [65].…”
Section: Non-genetic Factors For Scarsmentioning
confidence: 99%